The Factor V Gene A4070G Mutation and the Risk of Venous Thrombosis - Alhenc-Gelas, Martine; Nicaud, Viviane; Gandrille, Sophie; van Dreden, Patrick; Amiral, Jean; Aubry, Marie-Laurence; Fiessinger, Jean-Noël; Emmerich, Joseph; Aiach, Martine (Thrombosis and Haemostasis, 1999)
The A4070G polymorphism in exon 13 of the factor V (FV) gene, which replaces His by Arg at position 1299 of the B domain, was recently shown to influence circulating FV levels and to contribute to the activated protein C (APC) resistance phenotype. We examined the impact of this polymorphism in a population of unselected patients with venous thromboembolic disease (VTE). The prevalence of the G4070 (R2) allele was determined in 205 patients and 394 healthy subjects of similar age and sex distribution. Thirty-seven patients (18%) were heterozygous for the R2 allele and 1 (0.5%) was homozygous. Forty-four controls (11.2%) were heterozygous for the R2 allele and 1 (0.2%) was homozygous. Thus, the allelic frequency was significantly higher in the patients with VTE than in the healthy controls, with respective values of 9.5% and 5.8%. The odds ratio was 1.8 (95% CI: 1.1-2.8, p = 0.02), pointing to an increased risk of VTE in carriers of the R2 allele. After excluding subjects with putative or confirmed gene defects (mainly the FV R506Q mutation), the R2 allele was still a risk factor for VTE in the remaining patients, with an odds ratio of 2.0 (95% CI: 1.2-3.5, p = 0.01), demonstrating that this polymorphism is itself a risk factor. This study also confirms that the R2 allele influences APC resistance (APCR) in the absence of the FV R506Q mutation.